Activities of Omadacycline and Comparator Agents against Staphylococcus aureus Isolates from a Surveillance Program Conducted in North America and Europe - Pfaller, Michael A. (Antimicrob Agents Chemother, 2017)
Omadacycline is a new broad-spectrum aminomethylcycline in late-stage clinical development for acute bacterial skin and skin structure infections and community-acquired bacterial pneumonia as a once-daily formulation taken orally or intravenously. In this study, omadacycline and comparator agents were tested against 502 isolates of Staphylococcus aureus selected from a 2014 global surveillance program, and the results were compared with those for 7,740 isolates from a 2010 surveillance program. For the 2014 isolates, testing was completed on 252 isolates from Europe and 250 isolates from North America. Each set of isolates was composed of ∼100 hospital-acquired methicillin-resistant Staphylococcus aureus (HA-MRSA) isolates (isolated >48 h after hospital admission), 100 community-acquired MRSA (CA-MRSA) isolates (isolated <48 h after hospital admission), and 50 methicillin-susceptible S. aureus (MSSA) isolates. The omadacycline MIC(50) and MIC(90) for all S. aureus collected during 2014 was 0.12 and 0.12 μg/ml, respectively. The MIC(90) values were identical for MRSA, HA-MRSA, and CA-MRSA (0.12 μg/ml). The MIC(90) values for isolates from 2010 for S. aureus, MRSA, and CA-MRSA were 0.25 μg/ml (0.5 μg/ml for HA-MRSA; 87.8% were at ≤0.25 μg/ml). All 2014 and 2010 MRSA isolates were susceptible to vancomycin, and ≥99.8% were susceptible to daptomycin, linezolid, and tigecycline. The activity of omadacycline was similar for North American and European isolates, including MRSA (CA-MRSA or HA-MRSA). There was no evidence for emerging resistance to omadacycline between 2010 and 2014. The potent activity of omadacycline against S. aureus indicates that omadacycline merits further study in serious infections where multidrug resistance may be a concern.